Preparation and performance of highly-conductive dual-doped Li7La3Zr2O12 solid electrolytes for thermal batteries - Wei Li; Shu Zhang; Xinya Bu; Jing Luo; Yi Zhang; Mengyu Yan; Ting Quan; Yanli Zhu (Green Energy & Environment, 2025)
Garnet Li7La3Zr2O12 (LLZO) electrolytes have been recognized as a promising candidate to replace liquid/molten-state electrolytes in battery applications due to their exceptional performance, particularly Ga-doped LLZO (LLZGO), which exhibits high ionic conductivity. However, the limited size of the Li+ transport bottleneck restricts its high-current discharging performance. The present study focuses on the synthesis of Ga3+ and Ba2+ co-doped LLZO (LLZGBO) and investigates the influence of doping contents on the morphology, crystal structure, Li+ transport bottleneck size, and ionic conductivity. In particular, Ga0.32Ba0.15 exhibits the highest ionic conductivity (6.11E-2 S cm−1 at 550 °C) in comparison with other compositions, which can be attributed to its higher-energy morphology, larger bottleneck and unique Li+ transport channel. In addition to Ba2+, Sr2+ and Ca2+ have been co-doped with Ga3+ into LLZO, respectively, to study the effect of doping ion radius on crystal structures and the properties of electrolytes. The characterization results demonstrate that the easier Li+ transport and higher ionic conductivity can be obtained when the electrolyte is doped with larger-radius ions. As a result, the assembled thermal battery with Ga0.32Ba0.15-LLZO electrolyte exhibits a remarkable voltage platform of 1.81 V and a high specific capacity of 455.65 mA h g−1 at an elevated temperature of 525 °C. The discharge specific capacity of the thermal cell at 500 mA amounts to 63% of that at 100 mA, showcasing exceptional high-current discharging performance. When assembled as prototypes with fourteen single cells connected in series, the thermal batteries deliver an activation time of 38 ms and a discharge time of 32 s with the current density of 100 mA cm−2. These findings suggest that Ga, Ba co-doped LLZO solid-state electrolytes with high ionic conductivities holds great potential for high-capacity, quick-initiating and high-current discharging thermal batteries.